Genocide and resistance Nr. 50(2) - Miknevičius, Gintautas; Rukšėnas, Alfredas; Kripienė, Enrika; Tamkevičius, Sigitas; Andrukaitienė, Irena; Grickevičius, Artūras; Jenciutė, Viktorija; Binkauskaitė, Gretė (Genocidas ir rezistencija, 2021)
Full issue